The Political Economy of US Aid to Pakistan - Mumtaz Anwar; Katharina Michaelowa (Hamburg Institute of International Economics (HWWA), 2004)
Variations of bilateral aid flows are difficult to explain on the basis of official development objectives or recipient need. At the example of US aid to Pakistan, this paper suggests alternative political economic explanations, notably the relevance of ethnic lobbying and the relevance of US business interests. Time series regressions for the period from 1980 to 2002 and logistic regressions based on votes for the Pressler and the Brown Amendment confirm the significance of these political economic determinants. While in case of the Pressler Amendment, the direct influence of population groups of Indian and Pakistani origins seems to have played a predominant role, the role of ethnic business lobbies appears to have dominated in the context of the Brown Amendment. Time series analysis also provides some evidence for the impact of US business interests based on FDI and exports, but these effects appear to be comparatively small.
Keywords: F35; D70; 330; Public Choice; ethnic lobbying; foreign aid; Entwicklungshilfe; US-Amerikanisch; Interessenpolitik; Ethnische Gruppe; Pakistan; Vereinigte Staaten